Abundant CpG-sequences in human genomes inhibit KIR3DL2-expressing NK cells - Pugh,Jason; Guethlein,Lisbeth; Parham,Peter (PeerJ, 2021)
Killer Immunoglobulin-like Receptors (KIR) comprise a diverse, highly polymorphic family of cell-surface glycoproteins that are principally expressed by Natural Killer (NK) cells. These innate immune lymphocytes fulfill vital functions in human reproduction and immune responses to viral infection. KIR3DL2 is an inhibitory NK cell receptor that recognizes a common epitope of the HLA-A3 and HLA-A11 class I glycoproteins of the major histocompatibility complex. KIR3DL2 also binds exogenous DNA containing the CpG motif. This interaction causes internalization of the KIR-DNA. Exogenous CpG-DNA typically activates NK cells, but the specificity of KIR3DL2-DNA binding and internalization is unclear. We hypothesized that KIR3DL2 binds exogenous DNA in a sequence-specific manner that differentiates pathogen DNA from self-DNA. In testing this hypothesis, we surveyed octameric CpG-DNA sequences in the human genome, and in reference genomes of all bacteria, fungi, viruses, and parasites, with focus on medically relevant species. Among all pathogens, the nucleotides flanking CpG motifs in the genomes of parasitic worms that infect humans are most divergent from those in the human genome. We cultured KIR3DL2+NKL cells with the commonest CpG-DNA sequences in either human or pathogen genomes. DNA uptake was negatively correlated with the most common CpG-DNA sequences in the human genome. These CpG-DNA sequences induced inhibitory signaling in KIR3DL2+NKL cells. In contrast, KIR3DL2+NKL cells lysed more malignant targets and produced more IFNγ after culture with CpG-DNA sequences prevalent in parasitic worms. By applying functional immunology to evolutionary genomics, we conclude that KIR3DL2 allows NK cells to differentiate self-DNA from pathogen DNA.
Keywords: HLA; KIR; NK cells; KIR3DL2; CpG-DNA; PAMP